Application of Technology Acceptance Model in Testing of Regional Financial Information System - Muhammad Husni; Anisa Fitriyanti; Kartini Kartini (Faculty of Economics and Business, Hasanuddin University, Makassar, Indonesia, 2023)
New Public Management emerged as a new paradigm that was a draft reform towards good governance. Good Governance can be achieved if public sector governance and public sector performance, each of which is a well-implemented financial transparency and accountability, are implemented. The purpose of this study was to determine the influence of Perceive Ease of Use and Useful Peerceived on the acceptance of Regional Financial Information Systems (RIFS). This research is conducted by quantitative analysis methods. The population in this study was all users of the Regional Financial Information System in Jeneponto Regency with a total of 44 users using saturated sample techniques. Data is analyzed using data quality tests, classical assumption tests and hypothesis tests. The results of the study showed that the RIFS revenue in the Jeneponto District Government Agency was influenced by the user's perception of the ease of use of information systems. In this case the state civil apparatus either as a financial operator or treasurer in the working area of the Jeneponto District Government agency. Simultaneously the perception of ease of use and usefulness affects the acceptance of RIFS. In this case the operator / user feels that RIFS is easy to use and useful in doing the job.